De uma fábrica de antigamente a uma indústria racionalizada : o processo de desenvolvimento da Ritter Alimentos - Beiser, Ana Cristina Pires (2012)
The main objective of this research is to explain the reasons Ritter Alimentos S.A. has always maintained its position in the market, since it is a family firm, founded in 1919, in Cachoeirinha, Rio Grande do Sul, considering many cycles in its development related to management, property as well as family relationships. The company is still in the market for more than 90 years and, due to this fact, it deserves to be treated in a special way, as a study subject. The analysis of the company, focusing on its longevity in the market, can unveil some factors that may justify, in a universal way, the existence, still, of many family enterprises. In the current research, we showed the differences between the generations that managed the industry, taking into consideration its founder, genre and parentage, leadership, enterprising spirit, technological innovation and work in the production sector. In order to understand the founder s cycle, we studied, in his origins, the breweries of the family and his history, as a brewer. The food industry, in the beginning, had to overcome many obstacles, trigged by the Second World War and the big flood that happened in 1941, in Porto Alegre. The next step to the other phase was related to the way the founder educated his daughters and sons-in-law, considering the succession process. Still, in the leadership cycle of the son-in-law succession, Fritz Bernhard Beiser, the business was not modernized, and the product, typically characterized as craft. Over the years, the industry developed the most modern technologies to all its line production in the 60s, and Fritz gave his three children the management of the company. Thus, the third cycle of the history of the company begins with participation of these new members, as shareholders of the industry. Even though they have to face many economic crises, the industry increased at the end of this phase. Eventually, the fourth generation, trying to develop may researches, changed the way that the company had been managed in many aspects, such as: the development of management and qualification programs, and the utilization of the best technological resources, leading to the automation in the production.